Emotional intelligence occupational stress and job performance of teachers - Anuradha, R. Vijaya (New Delhi Discovery Publishing House PVT. LTD., 2014)
"The present study aims to identify the emotional intelligence, occupational stress and job performance of teachers working at higher secondary level. For this purpose, the Emotional Intelligence Rating Scale developed by Poormina (2010) for special education teachers based on certain emotional competencies of Goleman (2001) was adopted and modified by the investigator in accordance with the need of the present study. Similarly, the Occupational Stress Rating Scale developed by Reddy (2007) which was adopted and modifies by Poormina (2010) for special education teachers has been used for the study. This scale has been re-modified here and there keeping in mind the requirements of the study and suitable for higher secondary teachers and utilised in the current study. Further, the researcher has developed the Job Performance Rating Scale of teachers to assess the job performance at higher secondary level."--Page 136.
Includes bibliographical references and index.
Keywords: Emotional intelligence -- India; High school teachers -- India -- Job stress; High school teachers -- Rating of -- India